Waterlogged the serious problem of overhydration in endurance sports - Noakes, Timothy 1949- (Champaign, IL Human Kinetics, 2012)
"Drink as much as you can, even before you feel thirsty." That's been the mantra to athletes and coaches for the past three decades, and bottled water and sports drinks have flourished into billion-dollar industries in the same short time. The problem is that an overhydrated athlete is at a performance disadvantage and at risk of exercise-associated hyponatremia (EAH)--a potentially fatal condition. Dr. Tim Noakes takes you inside the science of athlete hydration for a fascinating look at the human body's need for water and how it uses the liquids it ingests. He also chronicles the shaky research that reported findings contrary to results in nearly all of Noakes' extensive and since-confirmed studies. In Waterlogged, Noakes sets the record straight, exposing the myths surrounding dehydration and presenting up-to-date hydration guidelines for endurance sport and prolonged training activities. Enough with oversold sports drinks and obsessing over water consumption before, during, and after every workout, he says. Time for the facts--and the prevention of any more needless fatalities.
Chapter 1. Perspectives on Human Physiology and Hydration -- Chapter 2. Thirst as a Signal for Fluid Intake -- Chapter 3. Water's Role in Thermoregulation -- Chapter 4. Salt Balance in the Body -- Chapter 5. Emergence of the Sports Drink Industry -- Chapter 6. The Shaky Science of Hydration -- Chapter 7. Early Drinking Guidelines -- Chapter 8. Discovery of Exercise-Associated Hyponatremia -- Chapter 9. The Biology of EAH -- Chapter 10. EAH and EAHE on a Global Scale -- Chapter 11. Guidelines for Fluid Intake.
Includes bibliographical references
Also available in print version
Keywords: Water intoxication; Endurance sports -- Physiological aspects